2005
DOI: 10.1196/annals.1333.008
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of Chemical Pathways in the Maillard Reaction by 17O‐NMR Spectroscopy

Abstract: 17O-NMR spectroscopy was employed as an innovative method to help understand mechanistic pathways in sugar fragmentation. Elucidation of reaction mechanisms to final Maillard end products was achieved by starting from specific intermediates obtained by synthesis, such as 1-deoxy-D-erythro-hexo-2,3-diulose. This alpha-dicarbonyl was thermally treated in the presence of 17O-enriched water under alkaline conditions. The reaction products were monitored by 17O-NMR spectroscopy and their structures corroborated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
30
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 16 publications
3
30
0
Order By: Relevance
“…The Maillard reaction is commonly invoked to account for abiotic chemical transformations of organic matter3536, and is ubiquitous in baking, toasting, and cooking of foods and in vivo in mammalian organisms33343536373839. In general, the Maillard reaction starts from the condensation between the aldehydes of reducing saccharides and the amino-containing proteins or amino acids, and ultimately leads to the formation of brown nitrogenous polymers, known as melanoidins33343536373839. More interestingly, it had been well proven by nuclear magnetic resonance technique, mass spectroscopy, and elemental analysis that different reaction precursors led to nitrogenous polymers varied in chemical composition and structures3438.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The Maillard reaction is commonly invoked to account for abiotic chemical transformations of organic matter3536, and is ubiquitous in baking, toasting, and cooking of foods and in vivo in mammalian organisms33343536373839. In general, the Maillard reaction starts from the condensation between the aldehydes of reducing saccharides and the amino-containing proteins or amino acids, and ultimately leads to the formation of brown nitrogenous polymers, known as melanoidins33343536373839. More interestingly, it had been well proven by nuclear magnetic resonance technique, mass spectroscopy, and elemental analysis that different reaction precursors led to nitrogenous polymers varied in chemical composition and structures3438.…”
mentioning
confidence: 99%
“…In the present approach, starting materials were firstly transformed to nitrogenous polymers via the Maillard reaction pathway under specific conditions that is low moisture, high temperature, and moderate alkaline environment33343536373839. Nevertheless, extreme conditions such as concentrated sulfate and/or phosphate acids were commonly applied in previous methods for the direct carbonization of the starting materials424344.…”
mentioning
confidence: 99%
“…Due to the importance of Maillard reaction in the field of food and biological science, it has been studied with modern technologies. NMR is the powerful method for identification of Amadori rearrangement products; however, the various tautomers of the ketose moiety in the solution significantly hamper the interpretation of the NMR spectra 11 . Currently, mass spectrometry (MS) related techniques offer an alternative, highly sensitive method and become powerful for the analysis of glycated products in complex mixture.…”
mentioning
confidence: 99%
“…The chemical shifts ( values), given in parts per million (ppm), were referenced to the signals of the residual protons ( 2.50 ppm) and carbon atom ( C 39.5 ppm) in DMSO-6 . All 1D ( 1 H, 13 C, and DEPT-135) and 2D ( 1 H-1 H COSY, 13 C-1 H COSY, and NOESY) NMR measurements were performed using standard Bruker pulse sequences. Sweep widths of 5000 and 25000 Hz were used in 1 H and 13 C NMR, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Modern analytical techniques have been applied in structural characterization of ARPs, such as circular dichroism, infrared spectroscopy, fluorescence spectroscopy, mass spectrometry, and nuclear magnetic resonance (NMR) spectroscopy [12]. It has been found that the presence of tautomers in the ketose moiety of ARPs limits the structure determination by 1D 1 H and 13 C NMR due to the complexity of the spectra [13,14]. However, 2D NMR techniques can provide more information for the structural characterization of ARPs.…”
Section: Introductionmentioning
confidence: 99%